2020
DOI: 10.3390/su12219187
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management Practices and Service Provider Commitment of Green Hotel Service Providers: Mediating Role of Resilience and Work Engagement

Abstract: Although research on human resource management practices (HRMPs) has been ongoing for many years, studies have actually paid little attention to HRMPs and their contribution to the emotional side of the bottom line or commitment to the external environment, particularly the serial mediation of HRMPs. Hence, to fill this research void, this study extends social exchange theory, broaden-and-build theory and the conservation of resources (COR) theory in the context of green hospitality by proposing a novel concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 112 publications
(185 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, this study supports the role of green performance management in influencing the GWE, but it was that its impact is not high in comparison to other variables. These results are similar to the results of a recent study that indicated that these three practices are positively associated with work engagement (Arasli et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, this study supports the role of green performance management in influencing the GWE, but it was that its impact is not high in comparison to other variables. These results are similar to the results of a recent study that indicated that these three practices are positively associated with work engagement (Arasli et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…One important aspect of these practices is green HRM which can effect on different green behaviors of employees especially their work engagement (Network for Business Sustainabilty, 2021). Applying suitable green HRM practices through its effect on GWE will improve the competitive advantage of these organizations (Arasli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, HPWS may positively affect the workforce's level of job satisfaction. This is because extant literature points out that employees value HRM practices comprising HPWS such as work-life balance [49,56], rewards [57], job security [58], or training opportunities [37,57]. Furthermore, some evidence also supports the positive repercussions of whole systems of high-performance work practices on job satisfaction [17,23].…”
Section: The Role Of Job Satisfaction Between Hpws and Qolmentioning
confidence: 99%
“…To respond to Kahn's call [20], this study develops a dynamic model of JE development behavior with a longitudinal study. That is to say, the JE has been treated as a static (trait) variable (i.e., one point in time) in the previous studies [22][23][24]. The fundamental premise that individuals can change their level of JE as a function of the way they interpret and make sense of their work context [25] has remained relatively unexamined.…”
Section: Introductionmentioning
confidence: 99%